2012
DOI: 10.5384/sjovs.vol5i1p1-14
|View full text |Cite
|
Sign up to set email alerts
|

The Oculomotor Systems Ability to Adapt to Structural Changes Caused by the Process of Senescence: A Review

Abstract: Age-related binocular vision anomalies are frequently encountered during clinical examination of mature patients. Observations of both concomitant and incomitant restrictions in eye motility indicate that all oculomotor system levels are implicated, from cortical neurons down to extraocular muscles. The system can make adaptations in response to changes induced by growth and ageing, which it does by monitoring and adjusting its own performance. This adaptive mechanism, which is important for maintaining motili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 120 publications
0
6
0
Order By: Relevance
“…[49][50][51] In humans, they have been observed at both the proximal and distal muscle insertions of infants and mature individuals. 52 It was reported that this tendon nerve ending in extraocular muscles is composed of myelinated nerve fibers that penetrate the tendon and then turn back 180 degrees to divide into several approximately parallel running branches exclusively on the tip of multiply innervated muscle fibers. 49 Greater numbers of myotendinous cylinders are found within the horizontal rectus muscle when compared with the vertical rectus or oblique muscles.…”
Section: Palisade Endingsmentioning
confidence: 99%
“…[49][50][51] In humans, they have been observed at both the proximal and distal muscle insertions of infants and mature individuals. 52 It was reported that this tendon nerve ending in extraocular muscles is composed of myelinated nerve fibers that penetrate the tendon and then turn back 180 degrees to divide into several approximately parallel running branches exclusively on the tip of multiply innervated muscle fibers. 49 Greater numbers of myotendinous cylinders are found within the horizontal rectus muscle when compared with the vertical rectus or oblique muscles.…”
Section: Palisade Endingsmentioning
confidence: 99%
“…They stated that this interaction between the eyes and the neck/shoulder muscle may be a neural command between sustained eye-lens accommodation when fixating on a near target and the postural muscles in the neck and shoulder area, which is activated to stabilize gaze during visually demanding conditions, such as near-visual work. In line with this, proprioceptive information from the oculomotor muscles and from somatic neck muscles has been shown to be mutually influential (Biguer et al 1982 ; Bruenech et al 2012 ; Han and Lennerstrand 1995 , 1998 ). The eyes and the head are activated synchronously with eye movements when looking at a visual target (Biguer et al 1982 ), and proprioceptive signals (vibration) of different neck muscles induce eye movements (Han and Lennerstrand 1995 ).…”
Section: Discussionmentioning
confidence: 86%
“…This indicates that the oculomotor system can make muscle-force increments by activating one single muscle fiber at the time. This outranks all other somatic muscles in terms of motor control [15].…”
Section: The Neural Substrate For the Control Of Eye Movementsmentioning
confidence: 92%